Theoretical Analysis of the Efficiency of RV Reducer with Beveloid Gear - Wang Xin; Huang Qingjiu; Chen Bin; Hou Yingfeng (Jixie chuandong)
The cycloidal gear has many drawbacks such as difficulty processing,higher cost,a special requirement on the center distance between engagement pair. Though the beveloid gear RV reducer,all above drawbacks are overcome,the aspect of large backlash and low transmission efficiency remained to be improved.Therefore,improving the structure of existing beveloid gear RV reducer is put forward,the involute gear pair of high- speed stage in existing RV reducer is replaced of beveloid gear pair to adjust the backlash into optimum state. Then,by taking effect factors of meshing efficiency such as meshing angle,cone angle and modification coefficient as the design variables,also with the goal of improving transmission efficiency,an optimization and analysis of the beveloid gear RV reducer is carried out. At last,comparing the transmission performance of the new beveloid gear RV reducer designed with the ordinary beveloid gear RV reducer,which illustrated the efficiency of the new RV reducer is superior to others.